PENGUKURAN NILAI VISKOSITAS OLI MESRAN SAE 10–SAE50 UNTUK PENDINGIN TRANSFORMATOR DISTRIBUSI DENGAN PENAMPIL LCD - -, Mujiman (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
Lubrications 0il is the main support of the working of a machine. Not only that, even this oil also determine the performance and engine durability. The better quality oil is used, the better the performance and engine durability. Function not only as a lubricating oil, but also as a cooling and cleaning machinery. As a lubricant, lubricating oil (lubricating) all moving parts inside the machine to prevent direct contact among components which made of metal. In this case, the element, thickness (viscosity) isveryimportant.As coolant, oil must also be able to reduce the heat generated by friction antarlogam on a machine that moves, such as valve (valve) or bearing (ball bearing).